Standardization of Laparoscopic Total Mesorectal Excision for Rectal Cancer: A Structured International Expert Consensus. Issue 4 (April 2015) - Miskovic, Danilo; Foster, Jake; Agha, Ayman; Delaney, Conor P.; Francis, Nader; Hasegawa, Hirotoshi; Karachun, Alexey; Kim, Seon Hahn; Law, Wai Lun; Marks, John; Morino, Mario; Panis, Yves; et al.
Abstract : Objective: To establish a structured international expert consensus on a detailed technical description of the laparoscopic total mesorectal excision (TME). Background: Laparoscopic TME is a common surgical approach for the treatment of rectal cancer, but there is little agreement on technical details and standards. Methods: Sixty leading surgical experts from 5 different world regions with a median overall experience of 250 laparoscopic TME participated in this study. Four stages of mixed quantitative and qualitative consensus-finding methods were applied. (1) Semistructured expert interviews were independently analyzed by 2 assessors. (2) Consensus on the interview data was reached using reiterating questionnaires (Delphi method). (3) This was further refined in an interactive workshop. (4) Based on this meeting, a comprehensive text was drafted and final approval was sought by all experts. Findings: Three theme categories were identified in 9 detailed interviews (anatomical landmarks, description of tissue retraction, and operating strategies). Following 2 rounds of a 54-item questionnaire, 29 items achieved very high agreement (A* ≥90%), 14 with good agreement (≥80%), 13 with moderate agreement (≥50%), and 18 with little or no agreement (<50%). In the workshop, areas of agreement were consolidated and conclusions were sought for those with less agreement. The final document was approved after 2 further rounds of surveys by all respondents. Conclusions: This detailed and agreed technical description of laparoscopic TME may have implications on training, assessment, quality control, and future research. Abstract : Supplemental Digital Content is Available in the Text.The aim of this study was to establish an international expert consensus on a detailed technical description of the laparoscopic total mesorectal excision using a structured, scientific process. This may have implications on training, assessment, quality control, and future research.